Functionalized Graphitic Carbon Nitride Nanomaterials for Electrochemiluminescent Detection of Cancer Cells. Issue 11 (1st November 2022) - Xiang, Xinzhu; Tian, Libing; Zhu, Xiaodi; Zhong, Yuting; Xiao, Chuyi; Chen, Lichan; Zhou, Shu-Feng
Abstract : Biosensors capable of detecting cancer cell quantity is significant for cancer pathological investigation and prognosis. Herein, a facile electrochemiluminescent (ECL) biosensor is developed for cancer cell detection by comprehensively utilizing the features of functionalized graphitic carbon nitride (g-CN) nanomaterials like well film-forming capability and functionalization level tunability. The solid-state ECL biosensor is fabricated via a simple dropping-drying method by subsequent deposition of g-CN nanosheets/graphene oxide nanocomposites (CNNS/GO) as ECL emitter, folate functionalized g-CN quantum dots (FA-CNQDs) as cancer cell capture agent, and bull serum albumin (BSA) as blocker to prevent nonspecific binding on glassy carbon electrodes (GCEs). The strong and stable ECL emission of CNNS/GO along with the tunability of FA content in FA-CNQDs endow the ECL biosensor with competitive sensitivity, which is able to detect folate receptor-positive cancer cells (HepG2) in the concentration range of 10 2 − 10 4 cells ml −1 under optimal condition. Additionally, the proposed ECL biosensor shows high specificity, reproducibility and long-term stability as well as good reliability towards serum sample detection.